1996
DOI: 10.1055/s-2006-957815
|View full text |Cite
|
Sign up to set email alerts
|

Bisabolenes and Furanosesquiterpenoids of KenyanCommiphora kuaResin

Abstract: The isolation and structure determination of a new bisabolene, 2-methyl-5-(5'-hydroxy-1',5'-dimethyl-3'-hexenyl)phenol, together with known bisabolene, xanthorrhizol and furanosesquiterpenoids, 2- O-acetyl-8,12-epoxygermacra-1(10),4,7,11-tetraene and 2- O-methyl-8,12-epoxygermacra-1(10),4,7,11-tetraene, from gum exudate of Commiphora kua are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Moreover, a previous study on the chemical composition of another Soqotri Commiphora species, namely C. kua [ 21 ], showed the absence of the major components in C. ornifolia and C. parvifolia such as camphor, α-fenchol, caryophyllene oxide and hexadecanoic acid. Generally, the comparison of our data with those of literature showed that the main constituents of chemical composition of the two investigated endemic Commiphora oils were markedly different from that of other known Commiphora species e.g., C. myrrha, C. kataf, C. holtziana, C. shaerocarpa, C. kua , C. opobalsamum and C. africana [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The data obtained can be used as a chemotaxonomical marker for Commiphora sp.…”
Section: Resultssupporting
confidence: 43%
See 1 more Smart Citation
“…Moreover, a previous study on the chemical composition of another Soqotri Commiphora species, namely C. kua [ 21 ], showed the absence of the major components in C. ornifolia and C. parvifolia such as camphor, α-fenchol, caryophyllene oxide and hexadecanoic acid. Generally, the comparison of our data with those of literature showed that the main constituents of chemical composition of the two investigated endemic Commiphora oils were markedly different from that of other known Commiphora species e.g., C. myrrha, C. kataf, C. holtziana, C. shaerocarpa, C. kua , C. opobalsamum and C. africana [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The data obtained can be used as a chemotaxonomical marker for Commiphora sp.…”
Section: Resultssupporting
confidence: 43%
“…Such compounds e.g. α-pinene, β-pinene, p -cymene and α-thujene represented the most major compounds in many reported Commiphora oils [ 17 , 18 , 19 , 20 ]. Moreover, a previous study on the chemical composition of another Soqotri Commiphora species, namely C. kua [ 21 ], showed the absence of the major components in C. ornifolia and C. parvifolia such as camphor, α-fenchol, caryophyllene oxide and hexadecanoic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1 and 2 were identified on the basis of their spectral data. Compound 1 (0.09% yield from the resin) was previously reported from C. molmol and C myrrha (8) and compound 2 (0.01 % yield from the resin) from C erythraea (10), C. myrrha (10), C.mo!mol (11), and C.kua (12). NMR spectral data of Genetically altered obese diabetic mice (designated C57BL/ l<s-db/db) served as experimental animals according to our protocol (13).…”
mentioning
confidence: 76%
“…The other component (3) considered novel afforded a molecular ion peak in the MS at m/z 476, calculated to be C 30 H 52 O 4 . From a preliminary observation, its mass spectrum exhibited the main features of a dammarane triterpene 9) as evidenced by fragment peaks at m/z 376, 315, 208, and 207.…”
mentioning
confidence: 99%